Facile Determination of Molecular Structure Trends in Amphiphilic Core Corona Star Polymer Synthesis via Dielectric Property Measurement. Issue 15 (17th June 2016) - Hild, Frederic; Nguyen, Nam T.; Deng, Eileen; Katrib, Juliano; Dimitrakis, Georgios; Lau, Phei‐Li; Irvine, Derek J.
Abstract : The use of dielectric property measurements to define specific trends in the molecular structures of poly(caprolactone) containing star polymers and/or the interbatch repeatability of the synthetic procedures used to generate them is demonstrated. The magnitude of the dielectric property value is shown to accurately reflect: (a) the number of functional groups within a series of materials with similar molecular size when no additional intermolecular order is present in the medium, (b) the polymer molecular size for a series of materials containing a fixed core material and so functional group number, and/or (c) the batch to batch repeatability of the synthesis method. The dielectric measurements are validated by comparison to spectroscopic/chromatographic data. Abstract : This plot of real permittivity ( ε ′) value against temperature for star poly(caprolactine)s initiated with pentaerythritol ethoxylate/trimethylolpropane ethoxylate shows this dielectric property measurement can be used to demonstrate that: (a) star polymers synthesized using conventional and microwave heating result in very similar molecular structures, and (b) different star structures can be differentiated by this property.